Mechanisms of action of Sappan lignum for prostate cancer treatment: network pharmacology, molecular docking and experimental validation - Li, Wenna; Jiang, Honglin; Zhang, Weina; Sun, Qiuyue; Zhang, Qiaoli; Xu, Jingnan; Huang, Jinchang; Wan, Yuxiang (Frontiers in Pharmacology, 2024)
Background: Prostate cancer (PCa) is the most common non-cutaneous malignancy in men globally. Sappan lignum, which exists in the heartwood of Caesalpinia sappan L., has antitumor effects; however, its exact mechanism of action remains unclear. This study elucidated the underlying mechanisms of Sappan lignum in PCa through network pharmacology approaches and molecular docking techniques. Moreover, the therapeutic effects of Sappan lignum on PCa were verified through in vitro experiments. Methods: The constituent ingredients of Sappan lignum were retrieved from the HERB database. Active plant-derived compounds of Sappan lignum were screened based on gastrointestinal absorption and gastric drug properties. Disease targets for PCa were screened using unpaired and paired case datasets from the Gene Expression Omnibus. Intersection targets were used for gene ontology and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis. Core targets were identified through topological analysis parameters and their clinical relevance was validated through The Cancer Genome Atlas database. The affinity between the phytochemicals of Sappan lignum and core proteins was verified using the molecular docking technique. Validation experiments confirmed the significant potential of Sappan lignum in treating PCa. Results: Twenty-one plant-derived compounds of Sappan lignum and 821 differentially expressed genes associated with PCa were collected. Among 32 intersection targets, 8 were screened according to topological parameters. KEGG analysis indicated that the antitumor effects of Sappan lignum on PCa were primarily associated with the p53 pathway. The molecular docking technique demonstrated a strong affinity between 3-deoxysappanchalcone (3-DSC) and core proteins, particularly cyclin B1 (CCNB1). CCNB1 expression correlated with clinicopathological features in patients with PCa. Experimental results revealed that 3-DSC exhibited anti-proliferative, anti-migratory, and proapoptotic effects on 22RV1 and DU145 cells while also causing G2/M phase cell cycle arrest, potentially through modulating the p53/p21/CDC2/CCNB1 pathway.This research highlights the promising therapeutic potential of Sappan lignum in treating PCa, with a particular focus on targeting the p53 pathway.